Biodiversity Conservation in Mangrove Environment - Singh, B. P. (Indian Forester, 1994)
The paper describes the biodiversity and need of its conservation in mangrove areas. Different strategies suggested are habitat and species protection, legislation, public awareness, peripheral development and research cum extension measures. The paper discusses different problems of mangrove environment and suggests measures to solve them.